1970
DOI: 10.13057/nusbiosci/n070106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foliar application of algae extract and amino acids mixture on fenugreek plants in sandy and clay soils

Abstract: Abstract. Tarraf SA, Talaat IM, El-Sayed AEB, Balbaa LK. 2015. Influence of foliar application of algae extract and amino acids mixture on fenugreek plants in . Two pot experiments were conducted to study the effect of foliar application of algae extract and amino acids mixture on the growth and chemical constituents of fenugreek plants (Trigonella foenum-graecum L.). Plants were sprayed with different concentrations of algae extract (0.0, 2.5, 5.0 g/L) or equivalent of amino acids mixture (0.0, 0.625, 1.25 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 14 publications
3
23
0
1
Order By: Relevance
“…Phytohormones are small molecules that work as chemical messengers to regulate cellular activities in crops. Moreover, these compounds are able to influence metabolic processes, including photosynthesis, respiration, nucleic acid synthesis and nutrient uptake [116].…”
Section: Phytohormone-like Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytohormones are small molecules that work as chemical messengers to regulate cellular activities in crops. Moreover, these compounds are able to influence metabolic processes, including photosynthesis, respiration, nucleic acid synthesis and nutrient uptake [116].…”
Section: Phytohormone-like Activitiesmentioning
confidence: 99%
“…Some studies highlighted an association among greater nutrient uptake, higher biomass accumulation, and greater crop yields when microalgae are used as biofertilisers [15,16,149]. Different studies were performed to assess the effect of MBF on different crops such as rice, garlic (Allium sativum L.), fenugreek (Trigonella foenum-graecum L.) and tomato [14,116,150,151], due to their potential possible applications in the different agricultural cropping systems, and to improve the agricultural sustainability.…”
Section: Fertilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…favorable effect of microalgae might be predicated to its success providing the plants with necessary nutrients and phytohormones. Tarraf et al [29] showed that fenugreek plants treated with a foliar application of algae extract had a significantly increased the number of leaves and branches, plant height, and fresh and dry weight during the vegetative growth and flowering stages. Sharara and El-Aal [30] reported that microbial inoculation such as microalgae stimulated growth in the plants in 2 ways: 1) directly, through the production of plant hormones and an improved uptake of nutrients, or 2) indirectly, via microbial balance changes in the rhizosphere towards beneficial micro-organisms.…”
Section: Ilns Biostimulation and Overcoming The Abiotic Stresses In Pmentioning
confidence: 99%
“…Devido ao potencial das microalgas para uso em sistemas de produção mais sustentáveis como a agricultura orgânica e a agricultura biodinâmica, uma série de trabalhos foram realizados com o objetivo de avaliar o efeito de fertilizantes à base de microalgas em algumas culturas (ZODAPE et al, 2011;PAUDEL et al, 2012;SHALABY;EL-RAMADY, 2014;TARRAF et al, 2015;GARCIA-GONZALEZ;SOMMERFELD, 2015). Em muitos desses trabalhos observou-se efeito positivo desses produtos, quando aplicados principalmente via foliar, em culturas como pimenta (ALY; ESAWY, 2008), alho (SHALABY; EL-RAMADY, 2014), arroz (PAUDEL et al, 2012) e tomate (ZODAPE et al, 2011).…”
Section: Introductionunclassified